PROFIL EFEKTIVITAS DAN KEAMANAN REMDESIVIR DALAM PENATALAKSANAAN PASIEN COVID-19: SYSTEMATIC REVIEW - Achmad Nabil Hafidh Maftuhin, (2022)
Coronavirus disease 2019 (COVID-19) has become a global pandemic since March 2020. Many of the medical staff are still doubtful about the efficacy and safety of the antivirals in the management of COVID-19. Remdesivir was obtained emergency clearance (EUA) from the FDA. we carried out a systematic research review to evaluate safety profile and the efficacy of remdesivir. From the results of the study time to recovery had a significant difference RR 1.29 (95% CI 1.12-149[P<0.0001]), time to improvement was not significant HR 0.94 (95% CI 0.80-1 ,10[P=0.44]), patients discharged did not differ significantly between the remdesivir and placebo groups (RR: 1.27 (95% CI 1.10-1.49), The duration of hospitalization, a shorter duration of stay in the remdesivir group (median 12 days vs. 17 days), mortality was not significantly different, oxygen demand was significantly different in users of supplemental oxygen supplementation HR 0.850 (95% CI 0.798000.906[P<0.001]). For the Safety, there was no significant difference. the optimal time to recovery and the level of safety is still acceptable. It can be said that the efficacy of administering remdesivir is still not sufficient to provide the best service to COVID-19 patients and its safety is still acceptable.